Macroprudential Policies and Housing Price : A New Database and Empirical Evidence for Central, Eastern, and Southeastern Europe - Vandenbussche, Jerome (IMF Working Papers; Working Paper ;, 2012)
Several countries in Central, Eastern and Southeastern Europe used a rich set of prudential instruments in response to last decade's credit and housing boom and bust cycles. We collect detailed information on these policy measures in a comprehensive database covering 16 countries at a quarterly frequency. We use this database to investigate whether the policy measures had an impact on housing price inflation. Our evidence suggests that some-but not all-measures did have an impact. These measures were changes in the minimum CAR and non-standard liquidity measures (marginal reserve requirements on foreign funding, marginal reserve requirements linked to credit growth).